Experience of gastroenteritis in Korean children: Single-center study - Seung Hyeon Seo; Yeoun Joo Lee; Sang Wook Mun; Jae Hong Park (Kosin Medical Journal, 2018)
Objectives Although Campylobacter is the main cause for bacterial acute gastroenteritis (AGE), there has been no notable clinical research into it, especially for Korean children. In this study, we share our experience of clinical, laboratory and image findings with Campylobacter AGE. Methods Between May 2013 and June 2016, children diagnosed as having Campylobacter AGE were retrospectively enrolled in our study. Campylobacter AGE was considered diagnosed when a patient had symptoms of bacterial AGE and a positive Campylobacter result in stool using multiplex PCR. Results Among 539 patients with suspected bacterial AGE, 31 (5.8%) patients had a positive result for Campylobacter. The average age of the 31 patients was 10.2 ± 5.0 years with a range between 1.1 and 16.9 years. Eighteen (58%) of the total patients were hospitalized between June and August. Diarrhea (93.5%), abdominal pain (83%) and fever (83%) were common symptoms. For 20 patients (65%), diarrhea lasted for less than three days, and fever lasted for 2.1 days on average. Among the 20 patients subjected to imaging studies, 12 patients (60%) showed bowel wall thickening on the right side of colon. In blood tests of 30 patients, 22 (73%) and 29 (97%) patients exhibited leukocytosis and elevated C-reactive protein, respectively. During treatment for Campylobacter AGE, prediagnostic empirical antibiotics were used for 6 (19%) patients. All patients recovered without complications. Conclusions Among the children with suspected bacterial AGE, 5.8% had a positive result on Campylobacter in stool using multiplex PCR. Therefore, we observe that Campylobacter AGE should be considered in school-age children who have diarrhea, fever, and abdominal pain.